Uzbekistan : Background Paper and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1995)
This Background Paper and Statistical Appendix highlights that starting in 1994, financial policies in Uzbekistan were tightened so as to reduce inflation and stabilize the exchange rate in anticipation of the introduction of the new national currency, the sum. The Central Bank of Uzbekistan raised the interest rate on its rediscount credits several times and credit to loss-making state enterprises was curtailed. The average monthly rate of price increase fell from more than 22 percent in the first half of the year to less than 2 percent in the third quarter, partly in reflection of seasonal factors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet